The Effect of Happiness and Positive Organizational Behavior on Productivity in the Workplace - Sri Wahyuningsih; Sotya Partiwi E; Wenny Marlini; Siti Nur Azizah (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study analyzes the effect of happiness and organizational behavior on employee productivity in the workplace. The research involved 123 employee respondents from seven Indonesian provinces and applied the Partial Least Squares Structural Equation Model (PLS-SEM) for data analysis. The results show that employees’ feelings of happiness and positive organizational behavior positively influence work productivity in the studied workplaces. Happiness in the workplace reflects feelings of pleasure, sincerity, and commitment in performing job duties, which in turn enhances performance. Likewise, positive organizational behavior plays a crucial role in shaping employee attitudes through positive culture, work environment norms, and effective communication, ultimately improving productivity. The findings confirm that happiness can motivate employees to create positive value and contribute meaningfully to organizational success, while positive organizational behavior strengthens performance through supportive psychological and social factors. These findings imply that psychological capital components play a critical role in enhancing employee productivity and positive organizational behavior. Strengthening happiness, self-efficacy, hope, resilience, and optimism within the workplace can serve as an effective strategic approach for organizations to improve individual performance and organizational outcomes.